(untitled) (Journal of Plant Disease Sciences, 2019)
Soybean (Glycine max (L.) Merrill) belongs to the family Leguminaceae. It is unique crop having versatile nutritional attribute yielding in both oil and protein.The experiment was laid out in Completely Randomized Design (CRD) with 8 treatments and three replications. In the present investigation three seed samples were collected viz., JS 335, Local-1 and Local-2 from Agril. Research Centre, Amravati and tested by standard blotter paper method (ISTA, 1966). The treated and untreated seed samples of soybean showed association of eight fungi belonging to six genera viz., Alternaria alternata, Curvularia lunata, Rhizoctonia bataticola, Fusarium moniliforme, Fusarium oxysporum, Aspergillus niger, Aspergillus flavus and Phomopsis sp. In comparative study of seed health testing methods viz.,blotter paper method and 2, 4-D blotter paper method, the blotter paper method was found superior in detection of seed mycoflora of soybean with maximum fungal load. The efficacy of fungicides and bioagents on seed-borne mycoflora, seed germination, shoot-root length and seedling vigour index were entimated and observed that the fungal association of soybean seed decreased in the seed treatment of benomyl @ 3 g kg-1 over all the other treatments.